(untitled) (Bangladesh Journal of Medical Science, 2016)
Background: Diabetes is associated with a high risk of cardiovascular diseases and underlying lipid abnormalities. Dyslipidemia, a modifiable risk factor is often underdiagnosed and undertreated in our patients. Its early identification can make aggressive cardiovascular preventive management possible. This report seeks to determine the prevalence and pattern of lipid abnormalities in type II diabetes mellitus. Methods: The lipid profiles and fasting blood sugar values of 100 known diabetics were studied. Their serum samples were assessed for fasting blood glucose [FBG], total cholesterol [TC], triacylglycerol [TG], low density lipoprotein cholesterol [LDL-C] and high density lipoprotein cholesterol [HDL-C] by using standard biochemical methods. Results: 83% of study subjects had lipid abnormalities. The mean TC, TG, LDL-C, and FBG levels were highly significant in the diabetics as compared to those in controls. It was found that 28% had hypercholesterolemia and 44% had hypertriglyceridemia. The mean HDL-C concentration was significantly high in female diabetics as compared to that in male diabetics. The correlation studies showed a non-significant negative correlation of FBG with TC, TG and LDL-C. Conclusion: In the diabetics, higher frequencies of high TC, high TG and high LDL-C levels are noted indicating diabetic patients were more prone for dyslipidemia which could cause cardiovascular disorders. Bangladesh Journal of Medical Science Vol.15(1) 2016 p.99-102